FT-IR analysis on the inclusion complex of Β-Cyclodextrin with quercetin, naringenin, 3-Hydroxyflavone and chrysin via different preparation methods / Noor Amilia Khosim, Ainnie Rahayu Abdullah and Marina Mokhtar - Khosim, Noor Amilia; Abdullah, Ainnie Rahayu; Mokhtar, Marina (Universiti Teknologi MARA, Pulau Pinang, 2015)
Flavonoids are used widely in the pharmaceutical industry due to their anti-oxidative and anti-inflammatory properties. However, most of the flavonoids are poorly water-soluble. These experiments were conducted to prepare the inclusion complex of β-Cyclodextrin with selected flavonoids such as Quercetin, Naringenin, 3-Hydroxyflavone and Chrysin. The methods used in complexing the host and guest molecules are modified physical mixture, kneading and freeze drying method by using the molar ratio of 1:1. The complexations of the flavonoids tested were analyzed by the Fourier Transform Infrared (FT-IR)spectroscopy. Analysis results suggested that the best method to complex β-Cyclodextrin with Quercetin and Chrysin, were via modified kneading method. Complexation of Naringenin and 3-Hydroxyflavone was best done via modified freeze drying and physical mixture method respectively.